2005
DOI: 10.1002/nbm.957
|View full text |Cite
|
Sign up to set email alerts
|

1H NMR spectroscopy in the diagnosis of Pseudomonas aeruginosa‐induced urinary tract infection

Abstract: The utility of (1)H NMR spectroscopy is suggested and demonstrated for the diagnosis of Pseudomonas aeruginosa in urinary tract infection (UTI). The specific property of P. aeruginosa of metabolizing nicotinic acid to 6-hydroxynicotinic acid (6-OHNA) is exploited. The quantity of 6-OHNA produced correlates well with the viable bacterial count. Other common bacteria causing UTI such as Escherichia coli, Klebsiella pneumonia, Enterobacter aerogenes, Acinetobacter baumanii, Proteus mirabilis, Citrobacter frundii,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 15 publications
0
28
0
Order By: Relevance
“…Interestingly, tyrosine and valine were only excreted into LB and not in SCFM. Finally, the increase of 6-hydroxynicotinic acid in P. aeruginosa cultures is probably due to limited catabolism of NAD or niacin and has been used as a diagnostic marker of P. aeruginosa infection (20).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, tyrosine and valine were only excreted into LB and not in SCFM. Finally, the increase of 6-hydroxynicotinic acid in P. aeruginosa cultures is probably due to limited catabolism of NAD or niacin and has been used as a diagnostic marker of P. aeruginosa infection (20).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recently Gupta et al, using the 1 H NMR metabolic approach, identified and quantified E. coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, and Proteus mirabilis isolates in urine samples from patients with urinary tract infections (UTIs) faster than using culture methods. This NMR method of metabolic profile exploration in urine provided an alternative approach for screening and identification of UTI (31)(32)(33)(34). These perspectives, along with the study reported in this paper, suggest the great potential of 1 H NMR for antimicrobial analysis.…”
Section: Discussionmentioning
confidence: 69%
“…After another 30 min of incubation, uroepithelial cells were washed with 50 ml PBS. Bacterial cells in washed PBS were counted by standard pour plate method [17][18][19].…”
Section: Hemagglutination Assaymentioning
confidence: 99%
“…For this 500 ll of the bacterial suspension and 500 ll of normal saline (in place of proanthocyanidin solution) were mixed and inoculated in a cell culture flask. After 30 min of incubation, uroepithelial cells were washed; bacterial cells in the washed PBS were counted, as described previously [17][18][19].…”
Section: Hemagglutination Assaymentioning
confidence: 99%